A Socio-Technical System (STS) Framework for Modular Construction of Cognitive Buildings. Issue 7 (1st November 2022) - Ghansah, F A; Lu, W; Chen, J; Peng, Z
Abstract: The cognitive building provides promises if its social and technical requirements are considered holistically, but these have not been consciously explored, particularly within modular construction, which offers an unexploited opportunity. This study, therefore, aims to develop a framework for the modular construction of a cognitive building as a socio-technical system to ensure effective human-technology interaction, stakeholder acceptance and engagement. The framework is examined with a mock-up project of a student smart residential building in Hong Kong, similar to a cognitive building, which adopted a modular construction technique. The case demonstrated that the framework effectively ensures multi-perspectival involvement of key stakeholders at the design and manufacturing phase to produce modular units cleanly embedded with appropriate and operable cognitive building technologies for users and facility managers before transported to the site. The study is based on a single case study; hence, there could be a little scientific rigour providing little basis for the generalisation of the results to a wider space. As buildings are technologically advancing, future studies are encouraged to look at other possible case projects that utilise modular construction principles and evaluate them by adopting this study's STS framework or its enhanced form.